1974
DOI: 10.1177/009524437400600102
|View full text |Cite
|
Sign up to set email alerts
|

Compounding Chlorinated Polyethylene Elastomers for High Temperature Service

Abstract: The inherent chemical inertness of peroxide cured, chem ically saturated CPE elastomers provides an opportunity for the formula tion of compounds with excellent resistance to high temperature environ ments. Data contained in this paper demonstrate that, with the proper choice of compounding ingredients, elongation and tensile losses less than 25% after aging 7 days at 302° F (150°C) in air can be attained. In the same compounds compression set can be kept below 30% (70 hrs at 302° F). To take advantage of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Similar investigation of the patent literature showed a sum of 500 records (according to SciFinder search). Although there are 150 patents related to flow photochemistry in the period from 1981 to 2004 (which does not line up with the journal articles analysis), these documents mostly feature high tonnage chemical processes [78][79][80][81][82] and polymers and films production [83][84][85][86] or wastewater treatment [87][88][89][90] . In order to properly fit this data with the journal paper analysis we did the same cut as before and found that the trend and numbers for the patents (Figure 1 E, chart in blue) are similar to the trends and numbers for papers.…”
Section: Introductionmentioning
confidence: 99%
“…Similar investigation of the patent literature showed a sum of 500 records (according to SciFinder search). Although there are 150 patents related to flow photochemistry in the period from 1981 to 2004 (which does not line up with the journal articles analysis), these documents mostly feature high tonnage chemical processes [78][79][80][81][82] and polymers and films production [83][84][85][86] or wastewater treatment [87][88][89][90] . In order to properly fit this data with the journal paper analysis we did the same cut as before and found that the trend and numbers for the patents (Figure 1 E, chart in blue) are similar to the trends and numbers for papers.…”
Section: Introductionmentioning
confidence: 99%